Experiencia subjetiva de la identidad de género de personas no binarias de Lima Metropolitana - Del Aguila Molina, Andrea (2021)
This qualitative research explores the subjective experience of a group of people who identify under the non-binary gender identity, which questions and differs from the female-male duality as a totalizing reality. A descriptive exploratory approach was used, through a phenomenological design. The sample consisted of 10 people, with an age range of 25 to 45 years, with characteristics of maximum variation. Through semistructured interviews, the experience in relation to non-binary identity, the perception of the participating people regarding living in a society built under the binary system and the concomitant repercussions of it, was studied in depth through a guide of 18 questions. The results were organized in four thematic areas: notion of gender, exploration and recognition, non-binary gender identity and repercussions of the binary system. It was found that gender identity is experienced as a reality bound to subjectivity of each individual, making it impossible to define it in exact normative parameters. People with non-binary gender identity coexist with an invalidating and stigmatizing social system, which makes them vulnerable to negative repercussions, both at a personal and social level, by experiencing and expressing their gender outside of the expected binary expectations. Therefore, support networks and coping strategies are essential for their well-being.